Basic gas chromatography - McNair, Harold Monroe, 1933-; Miller, James M., 1933-; Snow, Nicholas H., 1965- (John Wiley & Sons, Inc., 2019)
Basic Gas Chromatography, Third Edition provides a brief introduction to GC following the objectives for titles in this series. It should appeal to readers with varying levels of education and emphasizes a practical, applied approach to the subject. : This book provides a quick need-to-know introduction to gas chromatography; still the most widely used instrumental analysis technique, and is intended to assist new users in gaining understanding quickly and as a quick reference for experienced users. The new edition provides updated chapters that reflect changes in technology and methodology, especially sample preparation, detectors and multidimensional chromatography. The book also covers new detectors recently introduced and sample preparation methods that have become much more easily accessible since the previous edition.--Provided by publisher.